Educating Adolescents about Social Behavior using Information and Communications Technology - Vikas Rao Naidu; RAZA HASAN; Raya Al-Harrasi; Karan Jesrani (Sir Syed University Research Journal of Engineering and Technology, 2021)
The media has a wide range of applications. Information and Communications Technology (ICT) plays a vital role to educate the young generation. For over three decades, we have observed a very good involvement of media in spreading awareness on various issues pertaining to the society. The aim of this research study to seek the relationship between teaching multimedia (animation) at school level to educate adolescents about the social behavior. A survey has been carried out in five different levels of educational institution in Sultanate of Oman. 873 samples were collected, correlation analysis was performed on hypotheses to test the linear association. Linear regression has been performed to test hypothesis for comparing regression constants. The analysis discovered that there is adequate evidence to support the claim at the alpha level of significance that social behavior learning at school level on adolescents, multimedia effect on educating social behavior and technology aided support on learning of social behavior have a positive and significant effect having α=0.85, significance F = 0.0 and p value less than 0.05 proving to be significant.